Mechanism of MiR-145a-3p/Runx2 pathway in dexamethasone impairment of MC3T3-E1 osteogenic capacity in mice - Wu, Hang; Liao, Xinghua; Wu, Tingrui; Xie, Bin; Ding, Sicheng; Chen, Yiren; Song, Lijun; Wei, Bo (PloS one, 2024)
In this experiment, we screened key miRNAs involved in the dexamethasone-induced decrease in osteogenic capacity of mouse precursor osteoblasts MC3T3-E1 over and investigated their specific regulatory mechanisms. In this experiment, cell counting kit assay was utilized to act on MC3T3-E1 cells at 0, 5μM, 10μM, 15μM concentrations of dexamethasone for 24h, 48h and 72h to observe the changes in cell viability in order to select the appropriate dexamethasone concentration. Apoptosis and reactive oxygen species were detected by flow cytometry. The transcription of osteogenesis-related genes (Runx2, ALP, OCN, OPN, OPG, COL1A1) and protein expression levels (Runx2, ALP, OCN, OPN) were detected by Western Blot and qRT-PCR to validate the changes in cellular osteogenesis. The differentially expressed miRNAs related to MC3T3-E1 osteogenic differentiation after dexamethasone action were screened out. The expression levels of selected target miRNAs were verified in the experimental group and the control group by qRT-PCR. The miRNA inhibitor was transfected to knock down miRNA in dexamethasone-induced MC3T3-E1 injury. Alkaline phosphatase staining and flow cytometry were performed to detect apoptosis and reactive oxygen species changes. transcript and protein expression levels of osteogenesis-related genes in mouse MC3T3-E1 were detected by qRT-PCR and Western blot experiments. By miRNA target gene prediction, luciferase reporter gene experiments, qRT-PCR and Western blot experiments were used to verify whether the selected target miRNAs targeted the target gene. First, it was determined that 10μM dexamethasone solution was effective in inducing a decrease in osteogenic function in mouse MC3T3-E1 by CCK8 experiments, which showed a significant decrease in alkaline phosphatase activity, a decrease in calcium nodules as shown by alizarin red staining, an increase in apoptosis and reactive oxygen species as detected by flow cytometry, as well as a decrease in the expression of osteogenesis-related genes and proteins. Five target miRNAs were identified: miR-706, miR-296-3p, miR-7011-5p, miR-145a-3p, and miR-149-3p. miR-145a-3p, which had the most pronounced and stable expression trend and was the most highly expressed miRNA, was chosen as the target of this experiment by qRT-PCR analysis. -145a-3p, as the subject of this experiment. Knockdown of miR-145a-3p in MC3T3-E1 cells after dexamethasone action significantly improved the expression of their impaired osteogenic indicators. It was shown that after knocking down the target miRNA, alkaline phosphatase staining was significantly increased compared with the dexamethasone-stimulated group and approached the level of the blank control group. Meanwhile, the expression of osteogenic function-related proteins and genes also increased in the dexamethasone-stimulated group after knocking down miR-145a-3p, and approached the level of the blank control group. A direct targeting relationship between miR-145a-3p and Runx2 was indeed confirmed by luciferase reporter gene assays, qRT-PCR and Western blot experiments. The results indicated that dexamethasone impaired the osteogenic differentiation ability of MC3T3-E1 cells by inducing the up-regulation of miR-145a-3p expression. MiR-145a-3p inhibited the osteogenic differentiation ability of MC3T3-E1 cells by targeting and suppressing the expression level of Runx2 protein. Inhibition of miR-145a-3p levels significantly improved the osteogenic differentiation ability of MC3T3-E1 cells.